The knight at dawn - Osborne, Mary Pope.; Murdocca, Sal (New York : Scholastic, 1993)
Eight-year-old Jack and his younger sister Annie use the magic treehouse to travel back to the Middle Ages, where they explore a castle and are helped by a mysterious knight.
"This Scholastic edition is only available for distribution through the school market"--P. [4] of cover.
"RL: 2.2"--Cover p.[4].
310
Keywords: Time travel -- Fiction; Castles -- Fiction; Middle Ages -- Fiction; Knights and knighthood -- Fiction; Magic -- Fiction; Tree houses -- Fiction